IMPLEMENTASI PERATURAN WALI KOTA PADANG NOMOR 41 TAHUN 2017 TENTANG TATA CARA PEMBINAAN ANAK JALANAN PADADINAS SOSIAL KOTA PADANG - Riswanto Bakhtiar (Ekasakti Jurnal Penelitian dan Pengabdian, 2024)
Children under the age of 18, often characterized by a dull appearance and living on the streets, engage in activities such as selling newspapers, begging and busking to survive. This social problem arises because of social inequality and poverty, which makes it difficult for them to access the resources around them. In addition, a lack of religious education was also identified as a factor influencing these children, making them unable to face the trials. This research aims to analyze and propose solutions to improve the implementation program of Padang Mayor's regulation Number 41 of 2017 concerning procedures for developing street children which aims to prevent and overcome the problem of street children through various activities such as socialization, supervision and control. The research method used is a descriptive qualitative method where research provides an overview of individuals or groups regarding the conditions that occur. This data collection technique is through direct observation, interviews and documentation which provides an in-depth understanding of the condition of street children in Padang City. The results of the research and discussion show that in the implementation of Padang Mayor Regulation Number 41 of 2017 there are still obstacles that affect the effectiveness of the program, such as street children's lack of understanding of the regulations and limitations of the socialization approach. To overcome this problem, a more effective and intensive approach is needed in the socialization and assistance of street children as well as the importance of implementing a clear and consistent communication approach in the policy implementation process so that they can understand and follow the regulations well.